Contrasting Habitat Use and Population Dynamics of Reef Manta Rays Within the Nusa Penida Marine Protected Area, Indonesia - Germanov, Elitza S.; Bejder, Lars; Chabanne, Delphine B. H.; Dharmadi, Dharmadi; Hendrawan, I. Gede; Marshall, Andrea D.; Pierce, Simon J.; van Keulen, Mike; Loneragan, Neil R. (Frontiers in Marine Science, 2019)
Manta rays (Mobula spp.) are highly valued in nature-based tourism globally. In Indonesia, although manta rays are protected, critical information is lacking on their habitat use, population dynamics and movements. We investigate the population structure and residency patterns of reef manta rays (Mobula alfredi) in the Nusa Penida Marine Protected Area (MPA). From photo-identification data logged by citizen scientists and trained observers (mantamatcher.org), we identified 624 reef manta rays from 5,913 sightings (January 2012-April 2018) based on their unique ventral coloration patterns. Year-round records were collected from two shallow (< 20 m) reefs- Manta Bay (MB; n = 3,029 sightings) and Manta Point (MP; n = 3,058)- that are used frequently by tourism operators. Maximum likelihood techniques and a Markov movement analysis were used to model residency patterns and movement between these sites within the MPA. Manta rays at MB were predominantly male (64%, n = 261 individuals), with immature males (14%, n = 59) being sighted most frequently (39%, n = 1,170). In contrast, few immature individuals were sighted at MP (6%, n = 28), and they were sighed on few occasions (2%, n = 45), while mature female manta rays comprised 26% (n = 127) of the MP community and were the most frequently sighted (48%, n = 1,413). Lagged Identification Rates indicated high site fidelity at each location. However, 44% (n = 278) of individuals moved between the two sites and cumulative discovery curves showed a continued recruitment of individuals over the 6 years of the study. In addition, the behaviors displayed by the manta rays differed markedly between the two sites: MB appears to be a foraging ground, especially for juveniles, and potentially a nursery, while MP is used mainly for cleaning and courtship, indicating a social and reproductive site. Reproductive behavior coincided with the peak annual sightings in May. To prevent disturbance to this threatened species by tourism, regulations for the number of vessels and interactions, especially during key reproductive times should be considered. Further, strict fishing regulation in the area is recommended as fishing gear entanglement was identified as a threat to this population.